Assessment of greenhouse gas emissions of ventilated timber wall constructions based on parametric LCA. (1st October 2018) - Fufa, Selamawit Mamo; Skaar, Christofer; Gradeci, Klodian; Labonnote, Nathalie
Abstract: The increased use of multi-storey timber buildings can potentially create a significant reduction on the life cycle environmental impact of a building. However, with an increasing height of timber buildings the challenge is to maintain the same expected performance independent of the height; tall buildings are particularly exposed to high wind pressures combined with wind-driven rain. Additionally, tall buildings require longer construction times in which the structural elements are especially exposed to moisture. Furthermore, inspection, maintenance and repair possibilities are limited compared to low-rise buildings. This work develops a parametric life cycle assessment (LCA) methodology to evaluate the consequences (greenhouse gas (GHG) emissions) caused by a potential moisture damage of a failure event (considered as the mould and decay growth) in typical ventilated timber wall constructions from four countries: Germany (DE), France (FR), Norway (NO) and Sweden (SE). The environmental performance is evaluated throughout the life cycle of the wall construction in accordance with the modular system of life cycle stages as defined in EN 15978. Global warming potential (GWP) is used as a proxy for environmental impact. Product specific average environmental product declaration (EPD) is used as a main data source in GHG emission calculation. Three parameters; i) number of windows, ii) extent of damage around the window area and iii) the number of damaged layers; are used to evaluate the potential risk of GHG emission from moisture damage around window connections. A probabilistic-based design methodology is also applied to assess the mould and decay occurrence. The total GHG emission results from different scenarios considered in this study and the magnitude of environmental impact related to probabilistic damage are presented. The results show that GHG emissions increase with increase of the number of windows, the damaged area and the increase in the number of replaced layers. This is due to the additional GHG emissions from the materials used to replace the damaged layers. The probability of failure is sensitive to the defined unacceptable level of mould growth. This affects the risk assessment, where the perturbation derived from the different probabilities of failure for different layers are observed at the corresponding replacement interval. The results also show that the parametric results are sensitive to the variables used to estimate the area of replacement, the number of windows, the number of damaged layers and the considered failure event. This study can be used to evaluate and minimize the potential GHG emission of possible moisture damages scenarios on building envelopes. Furthermore, it can enable to consider various improvement measures that reduce the risk, resulting in a robust construction with good function, longer service life and lower embodied emissions during the building's life time. The study also highlights the need for further analysis of the assumptions and background data used when developing the parametric tool. Highlights: Parametric life cycle assessment is performed to evaluate moisture damage scenarios. Probabilistic-based methodology to include risk of mould and decay. Wall constructions from four different countries are evaluated. The probability of failure is sensitive to unacceptable level of mould growth. The parametric results are sensitive to the variables considered.